Two-component silicone sealant and preparation method thereof
By using raw materials such as α,ω-dihydroxypolydimethyldiphenylsiloxane and methylphenyl silicone oil with phenyl groups in the two-component silicone sealant, the instability problem of existing silicone sealant in high temperature and storage environment is solved, and the effect of high retention, good adhesion and low-precision glue machine is achieved.
Patent Information
- Application Number
- CN202411893631.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing two-component silicone sealant exhibits instability in storage and high temperature environments, and lacks adhesion to substrates, making it difficult to apply in high temperature-resistant places.
Using α,ω-dihydroxypolydimethyldiphenylsiloxane and methylphenyl silicone oil with phenyl groups, combined with α,ω-dihydroxypolydimethylsiloxane, alkoxy-terminated polydimethylsiloxane, active nanocalcium carbonate and nanoferrous oxide, two-component silicone sealant with stable storage, high initial strength and elongation of break are prepared through specific formulation design.
The silicone sealant still has a retention rate of more than 90% after baking at 300°C for 7 days. It has good adhesion, excellent adhesion to the substrate, and has stable performance under low-precision glue machine conditions.
Smart Images

Figure BDA0005201200830000011 
Figure BDA0005201200830000021 
Figure BDA0005201200830000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicone sealants, and in particular to a two-component silicone sealant and a preparation method thereof. Background Art
[0002] Silicone sealants absorb moisture from the air and cross-link to form high-molecular polymers with excellent performance. They are widely used in bonding and sealing in photovoltaic, construction, electronic appliances, rail transportation, and the automotive industry. They are an indispensable polymer material for the development of today's society. According to the packaging form, silicone sealants can be divided into single-component and two-component. In the two-component, due to the presence of trace amounts of moisture in component A, components A and B can be mixed and cured in a short time, greatly improving the transportation efficiency between various processes. At present, most of the mature two-component silicone sealant products on the market are dealcoholized, with poor storage and no high temperature resistance. The adhesion to the substrate is not as good as that of oxime glue, and it cannot be used in some places that require high temperature resistance, such as ovens, microwave ovens and other electronic and electrical products. Therefore, it is of great significance to develop a two-component product that has high temperature resistance and can be quickly cured in a short time. Summary of the invention
[0003] In view of the above-mentioned shortcomings, the present invention provides a two-component silicone sealant and a preparation method thereof, which has the advantages of stable storage, high initial strength and elongation at break, more than 90% retention rate after baking at 300°C for 7 days, good adhesion to the substrate, and low precision requirements for the glue machine.
[0004] In order to achieve the above object, the present invention provides a two-component silicone sealant, wherein the two-component silicone sealant is prepared by mixing component A and component B in a mass ratio of 1:1; in terms of mass fractions,
[0005] The raw material composition of the A component is:
[0006]
[0007] The raw material composition of the B component is:
[0008]
[0009]
[0010] The base glue A is compounded by α, ω-dihydroxy polydimethylsiloxane and α, ω-dihydroxy polydimethyl diphenylsiloxane.
[0011] According to one aspect of the present invention, the mass ratio of the α,ω-dihydroxypolydimethylsiloxane to the α,ω-dihydroxypolydimethyldiphenylsiloxane is 1:1-5:1.
[0012] According to one aspect of the present invention, the base glue B is compounded by alkoxy-terminated polydimethylsiloxane and methylphenyl silicone oil.
[0013] According to one aspect of the present invention, the mass ratio of the alkoxy-terminated polydimethylsiloxane to methylphenyl silicone oil is 1:1-5:1.
[0014] According to one aspect of the present invention, the viscosity of the α,ω-dihydroxy polydimethylsiloxane at 25°C is 1000-50000cp; the molar fraction of phenyl chains in the α,ω-dihydroxy polydimethyl diphenyl siloxane is 5%-30%, and the viscosity of the α,ω-dihydroxy polydimethyl diphenyl siloxane at 25°C is 5000-80000cp.
[0015] According to one aspect of the present invention, the filler is composed of active nano-calcium carbonate and nano-sized iron oxide; the mass ratio of the active nano-calcium carbonate to the nano-sized iron oxide is 1:1-5:1.
[0016] According to one aspect of the present invention, the particle size of the active nano-calcium carbonate is 10-50nm, and the active nano-calcium carbonate is obtained by surface-treating nano-calcium carbonate with a modifier; the modifier is one or more of stearic acid, silazane, silane coupling agent and titanate coupling agent; the particle size of the nano-scale iron oxide is 10-60nm.
[0017] According to one aspect of the present invention, the viscosity of the alkoxy-terminated polydimethylsiloxane at 25°C is 1000-50000cp; the molar fraction of phenyl chains in the methylphenyl silicone oil is 10%-60%, and the viscosity of the methylphenyl silicone oil at 25°C is 1500-20000cp.
[0018] According to one aspect of the present invention, the curing accelerator is at least one of sodium aluminum silicate, magnesium aluminum silicate, magnesium sulfate, and calcium chloride; the hydroxyl scavenger is hexamethyldisilazane; the crosslinking agent is at least one of phenyltributylacetonato silane, methyltributylacetonato silane, vinyltributylacetonato silane, tetrabutylketone oxime silane, methylvinyldibutylketone oxime silane, and methyltriacetone oxime silane; the coupling agent is γ-aminopropyltriethoxysilane, N-aminoethyl-γ-aminopropyltrimethoxysilane, The catalyst is at least one of dibutyltin dilaurate, dioctyltin dilaurate, hydroxydimethyltin, dimethyltin dilaurate, dibutyltin diacetate, and dibutyltin diisooctylmaleate.
[0019] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned two-component silicone sealant, comprising the following steps:
[0020] S1. Add α,ω-dihydroxy polydimethylsiloxane and α,ω-dihydroxy polydimethyl diphenylsiloxane into a planetary mixer and stir for 10-20 minutes to obtain a base rubber A;
[0021] S2, adding filler, curing accelerator and hydroxyl scavenger to base rubber A in sequence, stirring for 20-40 minutes under a vacuum degree of -0.090 MPa and removing bubbles to obtain component A;
[0022] S3, adding alkoxy-terminated polydimethylsiloxane and methylphenyl silicone oil into a kneader, stirring for 10-20 min at a vacuum degree of -0.090 MPa to obtain base rubber B;
[0023] S4, adding active nano-calcium carbonate to the base rubber B, dehydrating and stirring for 90-150 minutes at a temperature of 100-150° C. and a vacuum degree of -0.090 MPa by a kneader, and cooling to room temperature; adding a hydroxyl scavenger, a cross-linking agent, a coupling agent and a catalyst step by step to the cooled base rubber B and the active nano-calcium carbonate, stirring for 60-150 minutes at a vacuum degree of -0.090 MPa using a planetary machine, discharging and sealing for storage, to obtain component B;
[0024] S5. Mix component A and component B in a mass ratio of 1:1 to obtain a two-component silicone sealant.
[0025] Beneficial effects of the present invention:
[0026] The two-component silicone sealant of the present invention uses α, ω-dihydroxy polydimethyl diphenyl siloxane with phenyl groups and methyl phenyl silicone oil, and is matched with α, ω-dihydroxy polydimethyl siloxane, alkoxy-terminated polydimethyl siloxane, active nano calcium carbonate, nano-scale iron oxide, and curing accelerator, hydroxyl scavenger, crosslinking agent, coupling agent, and catalyst. Through a certain formula design, the two-component silicone sealant is obtained while taking into account the heat resistance, mechanical properties, and storage properties. Compared with the common dealcoholized two-component silicone sealant on the market, the present invention is a deoxime type, which has the characteristics of stable storage, high initial strength and elongation at break, and still has a retention rate of more than 90% after baking at 300°C for 7 days, and has good adhesion to the substrate. And the mixing ratio of the present invention is 1:1. After being applied to the market, the precision requirements for the glue machine are low, and the fluctuations of various properties after the AB components are mixed are small, which is conducive to the stability of the product. DETAILED DESCRIPTION
[0027] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.
[0028] Example 1
[0029] A two-component silicone sealant is prepared by mixing component A and component B in a mass ratio of 1:1; in terms of parts by weight,
[0030] Component A:
[0031] Base A:
[0032] α,ω-dihydroxypolydimethylsiloxane, 20000cp, 50 parts;
[0033] α,ω-dihydroxypolydimethyldiphenylsiloxane, 20000cp, 50 parts;
[0034] filler:
[0035] Active nano calcium carbonate, 20nm, 70 parts;
[0036] Nano iron oxide, 15nm, 70 parts;
[0037] Curing accelerator: sodium aluminum silicate, 6 parts;
[0038] Hydroxyl scavenger: hexamethyldisilazane, 1 part.
[0039] Component B:
[0040] Base B:
[0041] Alkoxy-terminated polydimethylsiloxane, 20,000 cp, 80 parts;
[0042] Methylphenyl silicone oil, 5000cp, 20 parts;
[0043] Active nano calcium carbonate: 20nm, 140 parts;
[0044] Hydroxyl scavenger: hexamethyldisilazane, 1 part;
[0045] Crosslinking agent:
[0046] Vinyltributylacetoximosilane, 4 parts;
[0047] Methyl tributylidene oxime silane, 13 parts;
[0048] Coupling agent:
[0049] N-aminoethyl-γ-aminopropyltrimethoxysilane, 3.5 parts;
[0050] 3-(2,3-Epoxypropyloxy)propyltrimethoxysilane, 1.5 parts;
[0051] Catalyst: di-n-butyltin diacetate, 0.2 parts.
[0052] A method for preparing a two-component silicone sealant comprises the following steps:
[0053] 50 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 20,000 cp and 50 parts of α, ω-dihydroxy polydimethyl diphenylsiloxane with a viscosity of 20,000 cp and a phenyl chain molar fraction of 5% are added to a planetary machine and stirred for 10 minutes to obtain base glue A; 70 parts of active nano calcium carbonate with a particle size of 20 nm and treated with stearic acid and titanate coupling agent, 70 parts of nano iron oxide with a particle size of 15 nm, 6 parts of sodium aluminum silicate and 1 part of hexamethyldisilazane are added to the base glue A, stirred for 30 minutes at a vacuum degree of -0.090 MPa and bubbles are removed to obtain component A.
[0054] 80 parts of alkoxy-terminated polydimethylsiloxane with a viscosity of 20,000 cp and 20 parts of methylphenyl silicone oil with a viscosity of 5,000 cp and a phenyl chain molar fraction of 30% were added to a kneader, stirred for 15 minutes at a vacuum degree of -0.090 MPa to obtain base rubber B; 140 parts of active nano-calcium carbonate with a particle size of 20 nm treated with stearic acid and titanate coupling agents were added to the base rubber B, dehydrated and stirred for 130 minutes at a temperature of 130°C and a vacuum degree of -0.090 MPa in a kneader, and cooled to room temperature. 1 part of hexamethyldisilazane, 4 parts of vinyltributylacetoximine silane, 13 parts of methyltributylacetoximine silane, 3.5 parts of N-aminoethyl-γ-aminopropyltrimethoxysilane, 1.5 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 0.2 parts of di-n-butyltin diacetate are added step by step to the cooled base glue B and active nano-calcium carbonate, and stirred for 130 minutes at a vacuum degree of -0.090 MPa using a planetary mill. The material is discharged and sealed for storage to obtain component B.
[0055] During construction, use glue-spraying equipment to evenly mix component A and component B in a mass ratio of 1:1.
[0056] Example 2
[0057] A two-component silicone sealant is prepared by mixing component A and component B in a mass ratio of 1:1; in terms of parts by weight,
[0058] Component A:
[0059] Base A:
[0060] α,ω-dihydroxypolydimethylsiloxane, 15000cp, 60 parts;
[0061] α,ω-dihydroxypolydimethyldiphenylsiloxane, 30000cp, 40 parts;
[0062] filler:
[0063] Active nano calcium carbonate, 25nm, 90 parts;
[0064] Nano iron oxide, 20nm, 50 parts;
[0065] Curing accelerator: magnesium aluminum silicate, 5 parts;
[0066] Hydroxyl scavenger: hexamethyldisilazane, 1 part.
[0067] Component B:
[0068] Base B:
[0069] Alkoxy-terminated polydimethylsiloxane, 15000cp, 75 parts;
[0070] Methylphenyl silicone oil, 3000cp, 25 parts;
[0071] Active nano calcium carbonate: 25nm, 140 parts;
[0072] Hydroxyl scavenger: hexamethyldisilazane, 1.5 parts;
[0073] Crosslinking agent:
[0074] Methyl tributylidene oxime silane, 5 parts;
[0075] Tetrabutyl ketoxime silane, 13 parts;
[0076] Coupling agent:
[0077] Bis(3-trimethoxysilylpropyl)amine, 3.5 parts;
[0078] 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 1.5 parts;
[0079] Catalyst: dibutyltin dilaurate, 0.25 parts.
[0080] A method for preparing a two-component silicone sealant comprises the following steps:
[0081] 60 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 15000cp and 40 parts of α, ω-dihydroxy polydimethyl diphenylsiloxane with a viscosity of 30000cp and a phenyl chain molar fraction of 10% are added to a planetary machine and stirred for 15 minutes to obtain base glue A; 90 parts of active nano calcium carbonate with a particle size of 25nm and treated with stearic acid and titanate coupling agent, 50 parts of nano iron oxide with a particle size of 20nm, 5 parts of aluminum magnesium silicate and 1 part of hexamethyldisilazane are added to the base glue A, stirred for 30 minutes at a vacuum degree of -0.090Mpa and bubbles are removed to obtain component A.
[0082] 75 parts of alkoxy-terminated polydimethylsiloxane with a viscosity of 15000cp and 25 parts of methylphenyl silicone oil with a viscosity of 3000cp and a phenyl chain molar fraction of 35% were added to a kneader, stirred for 10 minutes at a vacuum degree of -0.090Mpa to obtain base rubber B; 140 parts of active nano-calcium carbonate with a particle size of 25nm and treated with stearic acid and titanate coupling agents were added to the base rubber B, dehydrated and stirred for 120 minutes at a temperature of 120°C and a vacuum degree of -0.090Mpa by a kneader, and cooled to room temperature. 1.5 parts of hexamethyldisilazane, 5 parts of methyltributylacetoximine silane, 13 parts of tetrabutylketoxime silane, 3.5 parts of bis(3-trimethoxysilylpropyl)amine, 1.5 parts of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 0.25 parts of dibutyltin dilaurate are added step by step to the cooled base glue B and active nano-calcium carbonate, and stirred for 120 minutes at a vacuum degree of -0.090 MPa using a planetary mill. The material is discharged and sealed for storage to obtain component B.
[0083] During construction, use glue-spraying equipment to evenly mix component A and component B in a mass ratio of 1:1.
[0084] Example 3
[0085] A two-component silicone sealant is prepared by mixing component A and component B in a mass ratio of 1:1; in terms of parts by weight,
[0086] Component A:
[0087] Base A:
[0088] α,ω-dihydroxypolydimethylsiloxane, 12000cp, 70 parts;
[0089] α,ω-dihydroxypolydimethyldiphenylsiloxane, 25000cp, 30 parts;
[0090] filler:
[0091] Active nano calcium carbonate, 15nm, 70 parts;
[0092] Nano iron oxide, 25nm, 60 parts;
[0093] Curing accelerator: magnesium silicate, 5.5 parts;
[0094] Hydroxyl scavenger: hexamethyldisilazane, 1.5 parts.
[0095] Component B:
[0096] Base B:
[0097] Alkoxy-terminated polydimethylsiloxane, 12000cp, 77 parts;
[0098] Methylphenyl silicone oil, 2500cp, 23 parts;
[0099] Active nano calcium carbonate: 15nm, 130 parts;
[0100] Hydroxyl scavenger: hexamethyldisilazane, 1.6 parts;
[0101] Crosslinking agent:
[0102] Vinyltributylacetoximosilane, 4 parts;
[0103] Phenyltributylacetonatoximosilane, 13 parts;
[0104] Coupling agent:
[0105] γ-aminopropyltrimethoxysilane, 4 parts;
[0106] 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 2 parts;
[0107] Catalyst: dioctyltin dilaurate, 0.22 parts.
[0108] A method for preparing a two-component silicone sealant comprises the following steps:
[0109] 70 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 12000cp and 30 parts of α, ω-dihydroxy polydimethyl diphenylsiloxane with a viscosity of 25000 and a phenyl chain molar fraction of 15% are added to a planetary machine and stirred for 10 minutes to obtain base glue A; 70 parts of active nano calcium carbonate with a particle size of 15nm and treated with stearic acid and titanate coupling agent, 60 parts of nano iron oxide with a particle size of 25nm, 5.5 parts of magnesium silicate and 1.5 parts of hexamethyldisilazane are added to the base glue A, stirred for 35 minutes at a vacuum degree of -0.090Mpa and bubbles are removed to obtain component A.
[0110] 77 parts of alkoxy-terminated polydimethylsiloxane with a viscosity of 12000cp and 23 parts of methylphenyl silicone oil with a viscosity of 2500cp and a phenyl chain molar fraction of 40% were added to a kneader and stirred for 12 minutes at a vacuum degree of -0.090Mpa to obtain base rubber B. 130 parts of active nano calcium carbonate with a particle size of 15nm and treated with stearic acid and titanate coupling agents were added to the base rubber B, dehydrated and stirred for 125 minutes at a temperature of 130°C and a vacuum degree of -0.090Mpa by a kneader, and cooled to room temperature. 1.6 parts of hexamethyldisilazane, 4 parts of vinyltributylacetoximine silane, 13 parts of phenyltributylacetoximine silane, 4 parts of γ-aminopropyltrimethoxysilane, 2 parts of 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane and 0.22 parts of dioctyltin dilaurate are added step by step to the cooled base glue B and active nano-calcium carbonate, and stirred for 125 minutes at a vacuum degree of -0.090 MPa using a planetary mill. The material is discharged and sealed for storage to obtain component B.
[0111] During construction, use glue-spraying equipment to evenly mix component A and component B in a mass ratio of 1:1.
[0112] Example 4
[0113] A two-component silicone sealant is prepared by mixing component A and component B in a mass ratio of 1:1; in terms of parts by weight,
[0114] Component A:
[0115] Base A:
[0116] α,ω-dihydroxypolydimethylsiloxane, 20000cp, 50 parts;
[0117] α,ω-dihydroxypolydimethyldiphenylsiloxane, 20000cp, 50 parts;
[0118] filler:
[0119] Active nano calcium carbonate, 20nm, 70 parts;
[0120] Nano iron oxide, 15nm, 70 parts;
[0121] Curing accelerator: sodium aluminum silicate, 6 parts;
[0122] Hydroxyl scavenger: hexamethyldisilazane, 1 part;
[0123] Component B:
[0124] Base B:
[0125] Alkoxy-terminated polydimethylsiloxane, 20,000 cp, 80 parts;
[0126] Methylphenyl silicone oil, 5000cp, 20 parts;
[0127] Active nano calcium carbonate: 20nm, 140 parts;
[0128] Hydroxyl scavenger: hexamethyldisilazane, 1 part;
[0129] Crosslinking agent:
[0130] Vinyltributylacetoximosilane, 4 parts;
[0131] Methyl tributylidene oxime silane, 13 parts;
[0132] Coupling agent:
[0133] N-aminoethyl-γ-aminopropyltrimethoxysilane, 3.5 parts;
[0134] 3-(2,3-Epoxypropyloxy)propyltrimethoxysilane, 1.5 parts;
[0135] Catalyst: di-n-butyltin diacetate, 0.2 parts.
[0136] A method for preparing a two-component silicone sealant comprises the following steps:
[0137] 50 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 20,000 cp and 50 parts of α, ω-dihydroxy polydimethyl diphenylsiloxane with a viscosity of 20,000 and a phenyl chain molar fraction of 15% are added to a planetary machine and stirred for 10 minutes to obtain base glue A; 70 parts of active nano calcium carbonate with a particle size of 20 nm and treated with stearic acid and titanate coupling agent, 70 parts of nano iron oxide with a particle size of 15 nm, 6 parts of sodium aluminum silicate and 1 part of hexamethyldisilazane are added to the base glue A, stirred for 30 minutes at a vacuum degree of -0.090 MPa and bubbles are removed to obtain component A.
[0138] 80 parts of alkoxy-terminated polydimethylsiloxane with a viscosity of 20,000 cp and 20 parts of methylphenyl silicone oil with a viscosity of 5,000 cp and a phenyl chain molar fraction of 30% were added to a kneader, stirred for 15 minutes at a vacuum degree of -0.090 MPa to obtain base rubber B; 140 parts of active nano-calcium carbonate with a particle size of 20 nm treated with stearic acid and titanate coupling agents were added to the base rubber B, dehydrated and stirred for 130 minutes at a temperature of 130°C and a vacuum degree of -0.090 MPa in a kneader, and cooled to room temperature. 1 part of hexamethyldisilazane, 4 parts of vinyltributylacetoximine silane, 13 parts of methyltributylacetoximine silane, 3.5 parts of N-aminoethyl-γ-aminopropyltrimethoxysilane, 1.5 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 0.2 parts of di-n-butyltin diacetate are added step by step to the cooled base glue B and active nano-calcium carbonate, and stirred for 130 minutes at a vacuum degree of -0.090 MPa using a planetary mill. The material is discharged and sealed for storage to obtain component B.
[0139] During construction, use glue-spraying equipment to evenly mix component A and component B in a mass ratio of 1:1.
[0140] Example 5
[0141] A two-component silicone sealant is prepared by mixing component A and component B in a mass ratio of 1:1; in terms of parts by weight,
[0142] Component A:
[0143] Base A:
[0144] α,ω-dihydroxypolydimethylsiloxane, 15000cp, 60 parts;
[0145] α,ω-dihydroxypolydimethyldiphenylsiloxane, 30000cp, 40 parts;
[0146] filler:
[0147] Active nano calcium carbonate, 25nm, 70 parts;
[0148] Nano iron oxide, 20nm, 70 parts;
[0149] Curing accelerator: magnesium aluminum silicate, 5 parts;
[0150] Hydroxyl scavenger: hexamethyldisilazane, 2 parts.
[0151] Component B:
[0152] Base B:
[0153] Alkoxy-terminated polydimethylsiloxane, 15000cp, 75 parts;
[0154] Methylphenyl silicone oil, 3000cp, 25 parts;
[0155] Active nano calcium carbonate: 25nm, 140 parts;
[0156] Hydroxyl scavenger: hexamethyldisilazane, 3 parts;
[0157] Crosslinking agent:
[0158] Methyl tributylidene oxime silane, 5 parts;
[0159] Tetrabutyl ketoxime silane, 13 parts;
[0160] Coupling agent:
[0161] Bis(3-trimethoxysilylpropyl)amine, 3.5 parts;
[0162] 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 1.5 parts;
[0163] Catalyst: dibutyltin dilaurate, 0.25 parts.
[0164] A method for preparing a two-component silicone sealant comprises the following steps:
[0165] 60 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 15000cp and 40 parts of α, ω-dihydroxy polydimethyl diphenylsiloxane with a viscosity of 30000 and a phenyl chain molar fraction of 10% are added to a planetary machine and stirred for 15 minutes to obtain base glue A; 90 parts of active nano calcium carbonate with a particle size of 25nm and treated with stearic acid and titanate coupling agent, 50 parts of nano iron oxide with a particle size of 20nm, 5 parts of aluminum magnesium silicate and 2 parts of hexamethyldisilazane are added to the base glue A, stirred for 30 minutes at a vacuum degree of -0.090Mpa and bubbles are removed to obtain component A.
[0166] 75 parts of alkoxy-terminated polydimethylsiloxane with a viscosity of 15000cp and 25 parts of methylphenyl silicone oil with a viscosity of 3000cp and a phenyl chain molar fraction of 35% were added to a kneader, stirred for 10 minutes at a vacuum degree of -0.090Mpa to obtain base rubber B; 140 parts of active nano-calcium carbonate with a particle size of 25nm and treated with stearic acid and titanate coupling agents were added to the base rubber B, dehydrated and stirred for 120 minutes at a temperature of 120°C and a vacuum degree of -0.090Mpa by a kneader, and cooled to room temperature. 3 parts of hexamethyldisilazane, 5 parts of methyltributylacetoximine silane, 13 parts of tetrabutylketoxime silane, 3.5 parts of bis(3-trimethoxysilylpropyl)amine, 1.5 parts of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 0.25 parts of dibutyltin dilaurate are added step by step to the cooled base glue B and active nano-calcium carbonate, and stirred for 120 minutes at a vacuum degree of -0.090 MPa using a planetary mill. The material is discharged and sealed for storage to obtain component B.
[0167] During construction, use glue-spraying equipment to evenly mix component A and component B in a mass ratio of 1:1.
[0168] Comparative Example 1
[0169] This comparative example is a 1:1 two-component dealcoholized silicone sealant of a certain brand on the market.
[0170] Comparative Example 2
[0171] This comparative example is also a 1:1 deoxime type two-component silicone sealant, the difference is that the raw materials used are traditional 107 glue (α, ω-dihydroxy polydimethylsiloxane), dimethyl silicone oil and active nano calcium carbonate. Specifically:
[0172] Component A:
[0173] α,ω-dihydroxypolydimethylsiloxane, 20000cp, 100 parts;
[0174] Active nano calcium carbonate, 35nm, 140 parts;
[0175] Curing accelerator: sodium aluminum silicate, 6 parts;
[0176] Component B:
[0177] Base glue:
[0178] α,ω-dihydroxypolydimethylsiloxane, 20000cp, 80 parts;
[0179] Dimethicone oil, 5000cp, 20 parts;
[0180] Active nano calcium carbonate: 35nm, 140 parts;
[0181] Crosslinking agent:
[0182] Vinyltributylacetoximosilane, 4 parts;
[0183] Methyl tributylidene oxime silane, 13 parts;
[0184] Coupling agent:
[0185] γ-aminopropyltriethoxysilane, 3.5 parts;
[0186] 3-(2,3-Epoxypropyloxy)propyltrimethoxysilane, 1.5 parts;
[0187] Catalyst: di-n-butyltin diacetate, 0.2 parts;
[0188] A method for preparing a deoxime type two-component silicone sealant comprises the following steps:
[0189] 100 parts of α, ω-dihydroxy polydimethylsiloxane with a viscosity of 20,000 cp, 140 parts of active nano-calcium carbonate with a particle size of 35 nm, and 6 parts of sodium aluminum silicate were added to a planetary machine, stirred for 30 minutes at a vacuum degree of -0.090 MPa and bubbles were removed to obtain component A.
[0190] 80 parts of α, ω-dihydroxypolydimethylsiloxane with a viscosity of 20000c and 20 parts of dimethyl silicone oil with a viscosity of 5000cp are added to a kneader and stirred for 15 minutes at a vacuum degree of -0.090Mpa to obtain a base rubber; 140 parts of active nano-calcium carbonate with a particle size of 35nm are added to the base rubber, dehydrated and stirred for 130 minutes at a temperature of 130°C and a vacuum degree of -0.090Mpa by a kneader, and cooled to room temperature. 4 parts of vinyl trisbutyl ketoxime silane, 13 parts of methyl trisbutyl ketoxime silane, 3.5 parts of γ-aminopropyl triethoxy silane, 1.5 parts of 3-(2,3-epoxypropoxy)propyl trimethoxy silane and 0.2 parts of di-n-butyl tin diacetate are added step by step to the cooled base glue and active nano-calcium carbonate, and stirred for 130 minutes at a vacuum degree of -0.090 MPa using a planetary mill. The material is discharged and sealed for storage to obtain component B.
[0191] During construction, use glue-spraying equipment to evenly mix component A and component B in a mass ratio of 1:1.
[0192] Comparative Example 3
[0193] The preparation method of this comparative example is basically the same as that of Example 1, the only difference being that the base rubber B in component B is a combination of α, ω-dihydroxy polydimethylsiloxane and methylphenyl silicone oil. Specifically:
[0194] Component A:
[0195] Base A:
[0196] α,ω-dihydroxypolydimethylsiloxane, 20000cp, 50 parts;
[0197] α,ω-dihydroxypolydimethyldiphenylsiloxane, 20000cp, 50 parts;
[0198] filler:
[0199] Active nano calcium carbonate, 20nm, 70 parts;
[0200] Nano iron oxide, 15nm, 70 parts;
[0201] Curing accelerator: sodium aluminum silicate, 6 parts;
[0202] Hydroxyl scavenger: hexamethyldisilazane, 1 part.
[0203] Component B:
[0204] Base B:
[0205] α,ω-dihydroxypolydimethylsiloxane, 20000cp, 80 parts;
[0206] Methylphenyl silicone oil, 5000cp, 20 parts;
[0207] Active nano calcium carbonate: 20nm, 140 parts;
[0208] Hydroxyl scavenger: hexamethyldisilazane, 1 part;
[0209] Crosslinking agent:
[0210] Vinyltributylacetoximosilane, 4 parts;
[0211] Methyl tributylidene oxime silane, 13 parts;
[0212] Coupling agent:
[0213] N-aminoethyl-γ-aminopropyltrimethoxysilane, 3.5 parts;
[0214] 3-(2,3-Epoxypropyloxy)propyltrimethoxysilane, 1.5 parts;
[0215] Catalyst: di-n-butyltin diacetate, 0.2 parts.
[0216] A method for preparing a deoxime type two-component silicone sealant comprises the following steps:
[0217] 50 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 20,000cp and 50 parts of α,ω-dihydroxy polydimethyl diphenylsiloxane with a viscosity of 20,000 and a phenyl chain molar fraction of 5% were added to a planetary machine and stirred for 10 minutes to obtain base glue A. 70 parts of active nano calcium carbonate with a particle size of 20nm and treated with stearic acid and titanate coupling agent, 70 parts of nano iron oxide with a particle size of 15nm, 6 parts of sodium aluminum silicate and 1 part of hexamethyldisilazane were added to base glue A, stirred for 30 minutes at a vacuum degree of -0.090Mpa and bubbles were removed to obtain component A.
[0218] 80 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 20000cp and 20 parts of methylphenyl silicone oil with a viscosity of 5000cp and a phenyl chain molar fraction of 30% were added to a kneader and stirred for 15 minutes at a vacuum degree of -0.090Mpa to obtain base rubber B. 140 parts of active nano calcium carbonate with a particle size of 20nm and treated with stearic acid and titanate coupling agents were added to the base rubber B, dehydrated and stirred for 130 minutes at a temperature of 130°C and a vacuum degree of -0.090Mpa by a kneader, and cooled to room temperature. 1 part of hexamethyldisilazane, 4 parts of vinyltributylacetoximine silane, 13 parts of methyltributylacetoximine silane, 3.5 parts of N-aminoethyl-γ-aminopropyltrimethoxysilane, 1.5 parts of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 0.2 parts of di-n-butyltin diacetate are added step by step to the cooled base glue B and active nano-calcium carbonate, and stirred for 130 minutes at a vacuum degree of -0.090 MPa using a planetary mill. The material is discharged and sealed for storage to obtain component B.
[0219] During construction, use glue-spraying equipment to evenly mix component A and component B in a mass ratio of 1:1.
[0220] Comparative Example 4
[0221] The preparation method of this comparative example is basically the same as that of Example 3, the only difference being that the base rubber A in component A is all α,ω-dihydroxy polydimethyl diphenylsiloxane. Specifically:
[0222] Component A:
[0223] Base A:
[0224] α,ω-dihydroxypolydimethyldiphenylsiloxane, 25000cp, 100 parts;
[0225] filler:
[0226] Active nano calcium carbonate, 15nm, 70 parts;
[0227] Nano iron oxide, 25nm, 60 parts;
[0228] Curing accelerator: magnesium silicate, 5.5 parts;
[0229] Hydroxyl scavenger: hexamethyldisilazane, 1.5 parts.
[0230] Component B:
[0231] Base B:
[0232] Alkoxy-terminated polydimethylsiloxane, 12000cp, 77 parts;
[0233] Methylphenyl silicone oil, 2500cp, 23 parts;
[0234] Active nano calcium carbonate: 15nm, 130 parts;
[0235] Hydroxyl scavenger: hexamethyldisilazane, 1.6 parts;
[0236] Crosslinking agent:
[0237] Vinyltributylacetoximosilane, 4 parts;
[0238] Phenyltributylacetonatoximosilane, 13 parts;
[0239] Coupling agent:
[0240] γ-aminopropyltrimethoxysilane, 4 parts;
[0241] 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 2 parts;
[0242] Catalyst: dioctyltin dilaurate, 0.22 parts.
[0243] A method for preparing a deoxime type two-component silicone sealant comprises the following steps:
[0244] 100 parts of α, ω-dihydroxypolydimethyldiphenylsiloxane with a viscosity of 25,000 and a phenyl chain molar fraction of 15%, 70 parts of active nano-calcium carbonate with a particle size of 15 nm and treated with stearic acid and titanate coupling agents, 60 parts of nano-iron oxide with a particle size of 25 nm, 5.5 parts of magnesium silicate and 1.5 parts of hexamethyldisilazane are added to a planetary machine in sequence, stirred for 35 minutes at a vacuum degree of -0.090 MPa and bubbles are removed to obtain component A.
[0245] 77 parts of alkoxy-terminated polydimethylsiloxane with a viscosity of 12000cp and 23 parts of methylphenyl silicone oil with a viscosity of 2500cp and a phenyl chain molar fraction of 40% were added to a kneader and stirred for 12 minutes at a vacuum degree of -0.090Mpa to obtain base rubber B. 130 parts of active nano calcium carbonate with a particle size of 15nm and treated with stearic acid and titanate coupling agents were added to the base rubber B, dehydrated and stirred for 125 minutes at a temperature of 130°C and a vacuum degree of -0.090Mpa by a kneader, and cooled to room temperature. 1.6 parts of hexamethyldisilazane, 4 parts of vinyltributylacetoximine silane, 13 parts of phenyltributylacetoximine silane, 4 parts of γ-aminopropyltrimethoxysilane, 2 parts of 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane and 0.22 parts of dioctyltin dilaurate are added step by step to the cooled base glue B and active nano-calcium carbonate, and stirred for 125 minutes at a vacuum degree of -0.090 MPa using a planetary mill. The material is discharged and sealed for storage to obtain component B.
[0246] During construction, use glue-spraying equipment to evenly mix component A and component B in a mass ratio of 1:1.
[0247] Performance testing and result analysis:
[0248] The two-component silicone sealant prepared in the above embodiments and the comparative examples were tested using the following standards and methods, wherein the tensile strength and elongation at break were tested according to the requirements of Type 1 specimen (non-standard thickness) in GB / T 528-2009, the Shore A hardness was tested according to GB / T531-2008, the adhesion was tested according to Method 2 in Appendix D1.2 of GB 16776-2005, and the breaking time was tested according to Appendix D.5 of GB 16776-2005. The test results are shown in Tables 1 and 2.
[0249] Table 1 Comprehensive performance test results of various embodiments and comparative examples at room temperature
[0250]
[0251] Note: The bonding substrates are float glass, anodized aluminum and 304 stainless steel. √ indicates 100% cohesive failure, and × indicates 100% interfacial failure.
[0252] Table 2 Comprehensive performance test results of various embodiments and comparative examples baked at 300°C for 7 days
[0253]
[0254] Note: The bonding substrates are float glass, anodized aluminum and 304 stainless steel. √ indicates 100% cohesive failure, and × indicates 100% interfacial failure.
[0255] It can be seen from the data in Table 1-2 that the tensile strength and elongation at break of the two-component silicone sealant prepared in Examples 1-5, as well as the retention rate and storage performance after baking at 300°C for 7 days are better than those of Comparative Examples 1 and 2, wherein Comparative Example 1 is a dealcoholized two-component sealant, and the colloid shows powdering after baking at 300°C for 7 days, and the A and B components are subjected to accelerated aging at 90°C for 5 days, and the pulling time after mixing is 4.3 times that before aging, and the storage performance is far inferior to that of the embodiment of the present invention. Although Comparative Example 2 is also a deoxime-type two-component sealant, the formula raw materials are single, and the temperature resistance effect and storage performance are also inferior to those of the embodiment of the present invention. It can be seen from Comparative Example 3 and Example 1 that the solution of using alkoxy-terminated polydimethylsiloxane as the base glue of component B of the present invention can greatly improve the storage performance of the two components. As can be seen from Comparative Example 4 and Example 3, the base glue of component A of the present invention adopts α, ω-dihydroxy polydimethyl siloxane and α, ω-dihydroxy polydimethyl diphenyl siloxane for compounding and use, which can maintain the higher tensile strength and elongation at break of the colloid at room temperature, while taking into account the heat resistance. In addition, as can be seen from Example 1 and Example 4, the retention rate of mechanical properties after high temperature baking can be improved by improving the mole fraction of phenyl chains in α, ω-dihydroxy polydimethyl diphenyl siloxane and methylphenyl silicone oil, but the initial tensile strength will decrease and the elongation at break will increase. As can be seen from Example 2 and Example 5, the retention rate of mechanical properties after high temperature baking can be improved by improving the dosage of nano iron oxide and hexamethyldisilazane.
[0256] In summary, the present invention uses α, ω-dihydroxy polydimethyl diphenyl siloxane with phenyl groups and methyl phenyl silicone oil, and is matched with α, ω-dihydroxy polydimethyl siloxane, alkoxy-terminated polydimethyl siloxane, active nano-calcium carbonate and nano-iron oxide, as well as a curing accelerator, a hydroxyl scavenger, a cross-linking agent, a coupling agent, and a catalyst as raw materials. Through formula design for a two-component system for deketoxime, the mechanical property retention rate of the colloid after high-temperature baking can be significantly improved, while taking into account the excellent storage performance of the sealant and the mechanical properties at room temperature.
[0257] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A two-component silicone sealant, characterized in that: The two-component silicone sealant is prepared by mixing component A and component B in a mass ratio of 1:1; in terms of mass fractions, The raw material composition of the A component is: The raw material composition of the B component is: The base glue A is compounded by α, ω-dihydroxy polydimethylsiloxane and α, ω-dihydroxy polydimethyl diphenylsiloxane.
2. The two-component silicone sealant according to claim 1, characterized in that: The mass ratio of the α,ω-dihydroxy polydimethylsiloxane to the α,ω-dihydroxy polydimethyl diphenylsiloxane is 1:1-5:
1.
3. The two-component silicone sealant according to claim 1, characterized in that: The base glue B is compounded by alkoxy-terminated polydimethylsiloxane and methylphenyl silicone oil.
4. The two-component silicone sealant according to claim 3, characterized in that: The mass ratio of the alkoxy-terminated polydimethylsiloxane to the methylphenyl silicone oil is 1:1-5:
1.
5. The two-component silicone sealant according to claim 1, characterized in that: The viscosity of the α,ω-dihydroxy polydimethylsiloxane at 25°C is 1000-50000cp; the molar fraction of phenyl chains in the α,ω-dihydroxy polydimethyl diphenylsiloxane is 5%-30%, and the viscosity of the α,ω-dihydroxy polydimethyl diphenylsiloxane at 25°C is 5000-80000cp.
6. The two-component silicone sealant according to claim 1, characterized in that: The filler consists of active nano calcium carbonate and nano iron oxide; the mass ratio of the active nano calcium carbonate to the nano iron oxide is 1:1-5:
1.
7. The two-component silicone sealant according to claim 6, characterized in that: The particle size of the active nano calcium carbonate is 10-50nm, and the active nano calcium carbonate is obtained by surface treating the nano calcium carbonate with a modifier; the modifier is one or more of stearic acid, silazane, silane coupling agent and titanate coupling agent; the particle size of the nano-grade iron oxide is 10-60nm.
8. The two-component silicone sealant according to claim 3, characterized in that: The viscosity of the alkoxy-terminated polydimethylsiloxane at 25° C. is 1000-50000 cp; the molar fraction of phenyl chains in the methylphenyl silicone oil is 10%-60%, and the viscosity of the methylphenyl silicone oil at 25° C. is 1500-20000 cp.
9. The two-component silicone sealant according to claim 1, characterized in that: The curing accelerator is at least one of sodium aluminum silicate, magnesium aluminum silicate, magnesium sulfate, and calcium chloride; the hydroxyl scavenger is hexamethyldisilazane; the crosslinking agent is at least one of phenyltributylacetonato silane, methyltributylacetonato silane, vinyltributylacetonato silane, tetrabutylketone oxime silane, methylvinyldibutylketone oxime silane, and methyltriacetone oxime silane; the coupling agent is γ-aminopropyltriethoxysilane, N-aminoethyl-γ-aminopropyltrimethoxysilane, γ-aminopropyl The catalyst is at least one of dibutyltin dilaurate, dioctyltin dilaurate, hydroxydimethyltin, dimethyltin dilaurate, dibutyltin diacetate, and dibutyltin diisooctylmaleate.
10. The method for preparing a two-component silicone sealant according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: S1. Add α,ω-dihydroxy polydimethylsiloxane and α,ω-dihydroxy polydimethyl diphenylsiloxane into a planetary mixer and stir for 10-20 minutes to obtain a base rubber A; S2, adding filler, curing accelerator and hydroxyl scavenger to base rubber A in sequence, stirring for 20-40 minutes under a vacuum degree of -0.090 MPa and removing bubbles to obtain component A; S3, adding alkoxy-terminated polydimethylsiloxane and methylphenyl silicone oil into a kneader, stirring for 10-20 min at a vacuum degree of -0.090 MPa to obtain base rubber B; S4, adding active nano-calcium carbonate to the base rubber B, dehydrating and stirring for 90-150 minutes at a temperature of 100-150° C. and a vacuum degree of -0.090 MPa by a kneader, and cooling to room temperature; adding a hydroxyl scavenger, a cross-linking agent, a coupling agent and a catalyst step by step to the cooled base rubber B and the active nano-calcium carbonate, stirring for 60-150 minutes at a vacuum degree of -0.090 MPa using a planetary machine, discharging and sealing for storage, to obtain component B; S5. Mix component A and component B in a mass ratio of 1:1 to obtain a two-component silicone sealant.
Citation Information
Patent Citations
Neutral transparent silicone weather-resistant sealing adhesive for building
CN104232011A
Double-component silicone structural sealant
CN107805481A
High temperature resistance mould-proof silicone sealant and preparation method thereof
CN108676544A
High-strength bi-component flame-retardant silicone sealant and preparation method thereof
CN112812736A